Interpersonal Violence Experiences and Disclosure Patterns for Lesbian, Gay, Bisexual, Queer+, and Heterosexual University Students - Palmer, Jane E. (Journal of family violence, 2022)
We compare lesbian, gay, bisexual, and queer (LGBQ+; n = 355) to heterosexual (n = 1227) student experiences with victimization and disclosure. In spring of 2019, random samples of undergraduate and graduate students were invited to take an online victimization survey. Chi-square and logistic regression analyses were conducted to examine disclosure patterns of LGBQ+ and heterosexual students who experienced intimate partner violence or sexual violence. Among those with victimization experiences, we assessed differences in whether and to whom the LGBQ+ and heterosexual students disclosed these experiences. We find that a greater proportion of LGBQ+ students than heterosexual students experience intimate partner violence and sexual victimization in their lifetimes. In addition, a greater proportion of LGBQ+ students experienced sexual victimization since entering the university, before entering the university, in the past academic year, and revictimization. Similar proportions of LGBQ+ and heterosexual students told an informal resource (such as a friend or family member) about their victimization experience. However, in logistic regression models, LGBQ+ students (relative to heterosexual students) had greater odds of telling off-campus formal resources about intimate partner violence and sexual violence. They also had greater odds of telling on-campus formal resources about sexual violence, but not intimate partner violence. It is crucial that on-campus university prevention and intervention services are trauma-informed, inclusive, and anti-oppressive to prevent or mitigate short- and long-term impacts of victimization for vulnerable populations and promote disclosure. Universities must provide support services for intimate partner violence at the same level as sexual violence services.